Ralph Compton : reunion in Hell : a Ralph Compton western - Compton, Ralph; Stowers, Carlton (Compton, Ralph. Gunfighter series, 2020)
"A farmer is pulled into the world of outlaws when his estranged brother turns up dead in this new Ralph Compton Western. Brothers Clay and Cal Breckenridge, sons of a hardscrabble East Texas farmer, never did see eye to eye. Clay, the eldest, returned home after the Civil War to help his father run the family farm; Cal deserted his military post and disappeared into a new life with a new name. Everyone knew who was the good son and who was the bad. Clay had almost forgotten his wayward brother until the morning a limping horse approaches the farm with young Cal Breckenridge's body slumped in the saddle, shot in the back. Vowing to avenge Cal's death, Clay sets off on a perilous journey across the West to find the man responsible and bring him to justice--and take down an outlaw enterprise in the process."--Provided by publisher.